2020
DOI: 10.1109/jphot.2020.2968745
|View full text |Cite
|
Sign up to set email alerts
|

High Power Ho:YAP Laser With 107 W of Output Power at 2117 nm

Abstract: A high power Ho:YAP laser in-band pumped by a home-constructed Tm doped all fiber master oscillator power amplifier (MOPA) is reported. The optically polished and uncoated Ho:YAP laser yielded over 107 W of output power at ∼2117.1 nm with 215.4 W of absorbed pump power, corresponding to a slope efficiency of 50.6% with respect to the absorbed pump power. The beam quality M 2 parameter was measured at 80 W of output power to be ∼3.2 and ∼2.6 in x-and y-directions, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The design was based on three power amplification stages, thus generating a highest average output power of 73.1 W with 17 ns of pulse width, at a repetition rate of 3 kHz. Jinwen et al demonstrated a Ho: YAP laser excited by a Tm-doped MOPA system generating optical power of 107 W and slope efficiency (SE) of 50.6% at 2117.1 nm, for an absorbed pump power of 215.4 W [7]. Qian et al proposed a mid-infrared pulsed ZGP MOPA system operating at repetition rate of 2 kHz, while generating an output energy of 52 mJ [8].…”
Section: Introductionmentioning
confidence: 99%
“…The design was based on three power amplification stages, thus generating a highest average output power of 73.1 W with 17 ns of pulse width, at a repetition rate of 3 kHz. Jinwen et al demonstrated a Ho: YAP laser excited by a Tm-doped MOPA system generating optical power of 107 W and slope efficiency (SE) of 50.6% at 2117.1 nm, for an absorbed pump power of 215.4 W [7]. Qian et al proposed a mid-infrared pulsed ZGP MOPA system operating at repetition rate of 2 kHz, while generating an output energy of 52 mJ [8].…”
Section: Introductionmentioning
confidence: 99%
“…-SWITCHED Holmium (Ho) lasers are attractive in a variety of applications, such as lidar, surgeries and material processing [1]- [3], which are also the ideal pump sources for non-linear frequency conversion toward 3~14 μm via supercontinuum generation [4] and optical parameter oscillation [5]. Due to the lack of absorption band at 800 nm, Q-switched Ho lasers are mainly pumped by the Thulium (Tm) lasers and 1.9 μm diode lasers (LDs) [6], [7], especially in a MOPA structure with several well-developed high-power Tm lasers [8]. As additional layout for the Tm laser should be prepared for cascade pumping, compactness and accessibility of the pulsed Ho laser are limited [9].…”
Section: Introductionmentioning
confidence: 99%
“…In-band pumping of the unsensitized Ho-doped gain medium with 1.9 μm lasers had become a dominant way to achieve pulse operation at 2.1 μm for the past two decades [8]- [10], as the traditional Tm, Ho co-doped mechanism had severe upconversion losses at room temperature [11], [12].…”
Section: Introductionmentioning
confidence: 99%